Safeguarding Settler Colonialism in Geneva: Canada, Indigenous Rights, and ILO Convention No. 107 on the Protection and Integration of Indigenous Peoples (1957) - Meren, David (The Canadian Historical Review, 2021)
This article explores the intersecting of liberal internationalism and settler colonialism by tracing the Canadian governmental response to the emergence of International Labour Organisation (ilo) Convention 107 (1957) and Recommendation 104 (1957), the first international treaties regarding the rights of Indigenous Peoples in independent states. Drawing upon the archives of the ilo, Canada’s Department of External Affairs and Department of Citizenship and Immigration, notably the latter’s Indian Affairs Branch, the article investigates the convergence of mid-twentieth-century notions of Indigenous rights and the global phenomenon of “development.” It also explores how, amid anti-colonial resistance, decolonization, and an emerging international human rights regime, settler states responded, not least by seeking to blunt if not defeat the ilo initiative. In addition to yielding greater understanding of the origins and emergence of the ilo instruments, this analysis contributes to critical interrogations of Canadian liberal internationalism by revealing how Canadian settler preoccupations were projected abroad and shaped the international system’s evolving treatment of Indigenous Peoples. It also offers a different perspective on Canadian Indian policy by revealing the “global” dimension of an allegedly “domestic” question. Finally, the article highlights a parallel history of Indigenous internationalism speaking back to a world order constructed on Indigenous displacement and dispossession. Le présent article étudie les liens entre l’internationalisme libéral et le colonialisme de peuplement. À cette fin, il relate la réaction du gouvernement canadien devant l’émergence de la Convention 107 (1957) et la Recommandation 104 (1957) de l’Organisation internationale du Travail (oit), premiers traités internationaux portant sur les droits des peuples autochtones dans les États indépendants. À partir des archives de l’ oit, du ministère des Affaires extérieures et du ministère de la Citoyenneté et de l’Immigration du Canada, notamment de sa Division des affaires indiennes, l’article analyse la convergence entre les droits des autochtones, tels qu’ils étaient perçus au milieu du XXe siècle, et le phénomène mondial du « développement ». Il étudie également la manière dont les États colonisateurs, dans un contexte de résistance anticoloniale, de décolonisation et d’émergence d’un régime international des droits de l’homme, ont cherché à amoindrir, voire à faire échouer, l’initiative de l’oit. En plus de permettre de mieux comprendre les origines et l’émergence des instruments de l’oit, cette analyse aide à poser des questions pertinentes au sujet de l’internationalisme libéral canadien, car elle révèle comment les préoccupations des colonisateurs canadiens ont été projetées à l’étranger et ont joué un rôle dans l’évolution du traitement des peuples autochtones par le système international. Elle offre également une perspective différente sur la politique canadienne à l’égard des autochtones en révélant la dimension « mondiale » d’une question prétendument « intérieure ». Enfin, l’article met en lumière une histoire parallèle de l’internationalisme autochtone qui réagit à un ordre mondial construit sur le déplacement et la dépossession des autochtones.
Number: 2